Muppet treasure island - Ludlow, Anna (London : Muppet Press, 1996)
Set off the high seas with Jim Hawkins and his loyal friends. They are all desperate to eat to spooky skeleton island and find Captain Flint's buried treasure.
Based (very, very loosely) on the novel by Robert Louis Stevenson.
Keywords: Adventures -- fiction; Children stories